The Use of Auxiliaries in Optometric Practice - Griffith, F.H (Canadian Journal of Optometry, 1980)
As demand for health services increases and as capital and operating costs also increase the providers of health services must maximize their productivity while maintaining quality and patient satisfaction. The professions in Ontario, with the exception of optometry, make extensive use of auxiliaries as a means of increasing productivity. In the United States optometric assistants, trained in community and optometric colleges, are used widely. The paper presents a point of view urging the removal of restrictions on the appropriate use of well trained assistants.